Myeloid Leukemia - Lasfar, Ahmed (IntechOpen, 2018)
This book offers a remarkable coverage of myeloid leukemia from diagnosis to treatment. It provides an updated and new vision of this multifaceted disease, regrouping a variety of myeloid disorders. To ensure the high quality of this book, important insights are included and rigorously discussed in a simple and authentic way. This book is a relevant source of knowledge, very useful for researchers, medical doctors, nurses, students and individuals interested in this complex disease.